DOI: 10.31274/rtd-180813-8870
|View full text |Cite
|
Sign up to set email alerts
|

Wheat root rot in West Central Morocco and effects of Fusarium culmorum and Helminthosporium sativum seed and soil-borne inoculum on root rot development, plant emergence and crop yield

Abstract: Wheat root rot in West Central Morocco and effects of Fusarium culmorum and Helminthosporium sativum seed and soil-borne inoculum on root rot development, plant emergence and crop yield " (1988). Retrospective Theses and Dissertations. 8866.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
2
0
1
Order By: Relevance
“…La répartition géographique des différentes espèces du Fusarium ainsi notée en Tunisie, a été de même observée par différents auteurs dans diverses zones céréalières du monde, mais leurs distributions restent tributaires du microclimat local. En effet, au Maroc, Fusarium culmorum était présent dans presque 25% des champs (Lyamani, 1988). Cook (1967) a rapporté que F. culmorum exige plus d’humidité que F. graminearum .…”
Section: Discussionunclassified
“…La répartition géographique des différentes espèces du Fusarium ainsi notée en Tunisie, a été de même observée par différents auteurs dans diverses zones céréalières du monde, mais leurs distributions restent tributaires du microclimat local. En effet, au Maroc, Fusarium culmorum était présent dans presque 25% des champs (Lyamani, 1988). Cook (1967) a rapporté que F. culmorum exige plus d’humidité que F. graminearum .…”
Section: Discussionunclassified
“…Infection can also occur during grain storage or afterward (Hashem et al, 2010). In Morocco, several Fusarium species are associated with symptoms of root rot in cereals; the most common are F. equiseti, F. culmorum, F. oxysporum, and F. solani (Lyamani 1988).…”
Section: P O S T P R I N Tmentioning
confidence: 99%
“…Durum wheat ( Triticum durum Desf) damage commonly exceeds 50% reduction in grain yield ( Jones and Clifford 1978 ; Smiley et al, 2005 ). Many studies have shown that durum wheat is in fact the most sensitive crop to FRR in Morocco ( Lyamani, 1988 ; Mergoum, 1991 ; Nsarellah et al, 2000 ). Therefore, the main objective of this study was to find novel sources of resistance to Fusarium culmorum in durum wheat.…”
mentioning
confidence: 99%